Theoretical and experimental research on the impacts of the Joukowsky hydrofoils on the bubble collapse dynamics within a confined space - Junwei Shen; Hongbo Wang; Cheng Zhang; Yuning Zhang; Yuning Zhang (Ultrasonics Sonochemistry)
The present paper investigates the bubble collapse dynamics near hydrofoils within a confined space. Experiments involving high-speed photography reveal in detail the typical bubble morphological evolution near different hydrofoils between two glass plates (namely the confined space), and the partitioning of the thickness-related and camber-related parameters is analyzed quantitatively. Based on conformal transformation, the liquid velocity field and Kelvin impulse are used to analyze the bubble collapse characteristics qualitatively and quantitatively, including the bubble interface motion, cross-sectional roundness, and collapse jet. The main conclusions are summarized as follows. (1) The bubble morphological evolution near the hydrofoils can be categorized into five typical collapse shapes, and their partition ranges are significantly affected by the thickness-related and camber-related parameters. (2) The thickness-related hydrofoil parameter positively correlated with the bubble interface motion and cross-sectional roundness, while the camber-related parameter is inversely correlated with them. (3) High-velocity regions between the bubble and the hydrofoil head and tail endpoints explain the bubble interface depressions observed in the experiments.